Role of serum VEGF-A biomarker for early diagnosis of ovarian cancer instead of CA-125 - Nafeesa Maryam; Syed Shoaib Ahmed; Rabail Alam; Muhammad Umair Hanif; Mahjabeen Saleem; Roquyya Gul (Journal of the Pakistan Medical Association, 2021)
Objective: Vascular Endothelial Growth Factor-A (VEGF-A) is one of the most potent modulator and prominent mediator of angiogenesis and neovascularization. Present study focuses on the significance of VEGF-A as potential biomarker from serum for the diagnosis of non-therapeutic, pre-operative ovarian cancer patients in comparison with healthy individuals instead of Cancer Antigen-125 (CA-125). Methods: The study recruited total 89 subjects; 44 cases of epithelial ovarian cancer (31 malignant and 13 benign) and 45 healthy female controls under aseptic conditions. Serum VEGF-A and CA-125 levels were evaluated from each subject using Luminex multi-analyte profiling (xMAP) technology on BioPlex instrument and EIA technique, respectively. Different clinicopathological parameters; age, stage, grading, metastasis and ascites of ovarian cancer patients were investigated and compared with serum VEGF-A and CA-125 levels. Results: Our results showed that serum VEGF-A values were inversely proportional to the stage of ovarian cancer. However, steadily increase in the CA-125 values was observed with progression of the disease. Conclusion: The detection of highest concentration of serum VEGF-A level in FIGO (International Federation of Gynecology and Obstetrics) stage-I suggests its use as one of the diagnostic parameter in the timely investigation of ovarian cancer. Keywords: Ovarian cancer, VEGF-A, CA-125, Luminex multi-analyte profiling, EIA, FIGO Continuous....